PERILAKU COPING OLEH STREET LEVEL BUREAUCRAT PENANGANAN BENCANA COVID 19 DI KOTA BENGKULU (STUDI PADA BADAN PENANGGULANGAN BENCANA DAERAH) - Desita Rahayu; Romdana Romdana; Redho Rezki Marseven (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2022)
Street Level Bereucrats who usually handle disaster management received additional mandates as the task force for handling Covid 19 in accordance with policy of Bengkulu Mayor No. 167/2020. Having no experience in disasters pandemic and limited skills can cause problem in emergency services. This condition has caused street-level bureaucrats to do "coping behavioral". The locus of this research is Street Level Bereucrats of BPBD Bengkulu. This is a case study research in which Street Level Bereucrats as the population, and snowball sampling. The data used are primary and secondary data with interview techniques, observation and documentation study. The results showed that coping mechanism was done by Street Level Bereucrats in two ways: routines and simplification. The Routines mechanism are rationalizing services, client registration, and resources by placing personnel according to their skills and educational background, controlling risks, namely by improving disaster public service skills. The simplification mechanism is also carried out by simplifying work procedures, especially in emergency situations and preparing action plans that may have to be carried out.